The nexus between science and industry: evidence from faculty inventions - Dirk Czarnitzki; Katrin Hussinger; Cédric Schneider (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2009)
Against the background of the so-called European paradox, i.e. the conjecture that EU countries lack the capability to transfer science into commercial innovations, knowledge transfer from academia to industry has been a central issue in policy debates recently. Based on a sample of German scientists we investigate which academic inventions are patented by a scientific assignee and which are owned by corporate entities. Our findings suggest that faculty patents assigned to corporations exhibit a higher short-term value in terms of forward citations and a higher potential to block property rights of competitors. Faculty patents assigned to academic inventors or to public research institutions, in contrast, are more complex, more basic and have stronger links to science. These results may suggest that European firms lack the absorptive capacity to identify and exploit academic inventions that are further away from market applications.
Keywords: O31; O32; O34; 330; academic inventors; university-industry technology transfer; intellectual property rights; Hochschulforschung; Erfindung; Patent; Industrielle Forschung; Wissenstransfer; Technologietransfer; Forschungskooperation; Deutschland